TEMPERATURE AND NITRATE CONCENTRATION EFFECT ON THE ABUNDANCE AND GROWTH RATE OF MELOSIRA SP. - Nita Rukminasari; Sharifuddin Andy Omar; Muhammad Lukman (BIOLINK (Jurnal Biologi Lingkungan Industri Kesehatan), 2021)
Microalgae are one of the natural resources that have high potential as a source of biofuels, one of them is the marine microalgae Melosira sp.. The objective of this study was to determine the effect of increasing temperature and nitrate concentration on the abundance, growth rate, biomass, organic C-content and free fatty acids of Melosira sp.. A Completely Randomized Design was used for this experiment with four temperature treatments and three nitrate concentrations treatments  in microalgae test planting media. The test microalgae were cultured for 21 days, while the abundance of Melosira sp..was carried out every 3rd day, while for other parameters measurements were made at the end of the experiment. The results showed that the increasing in temperature and nitrate concentration in culture media significantly affected the abundance of Melosira sp.. Meanwhile, the results of statistical analysis showed that the increase in temperature and concentration of culture media did not have a significant effect on biomass except at 30°C treatment, the dry weight of Melosira sp. was only significantly different between the nitrate concentrations of 0.0 g/L and 0.4 g/L. For the content of C-organic and free fatty acids generally showed a significant difference between treating temperature and nitrate concentration in the culture media.